Rate of decline in Alzheimer's disease measured by a dementia severity rating scale - Xie, Sharon X. (2009)
OBJECTIVE: To measure clinically relevant change in Alzheimer's disease (AD) using a family member completed dementia severity rating scale (DSRS) questionnaire. BACKGROUND: Measuring rate of change provides important clinical information. Most neuropsychological scores change nonlinearly, complicating their use as a predictor of change throughout the illness. METHODS: DSRS and Mini Mental State (MMS) scores were prospectively collected on 702 patients with AD from first evaluation until they became too impaired to return to clinic. RESULTS: DSRS score increased an average of 4.48 points per year (95% CI 4.14 - 4.82) throughout the entire range of severity. In contrast, the MMS declined an average of 2.15 points per year (95% CI 1.85-2.46) during the first two years, accelerated to 3.83 points per year (95% CI 3.28-4.38) during the subsequent three years and then slowed to an annual decline of 1.63 points during the last two years (95% CI 0.21-3.05). A younger age of symptom onset was associated with an increased rate of DSRS change (p=0.03). CONCLUSIONS: The DSRS provides a clinical measure of functional impairment in AD that increases about 4.48 points per year from the earliest symptomatic stage until patients become too severely impaired to return to clinic.